Hiding the Elephant: The Tragedy of COVID Policy and Its Economist Apologists - Gigi Foster; Paul Frijters (Institute of Labor Economics (IZA), 2022)
In 2020 and 2021, the world witnessed policies that caused enormous net damage to nearly every country. We demonstrate the usefulness of the new WELLBY currency in gauging the costs and benefits of COVID policies and review the contributions of Australian economists to the scholarly and public debates about these policies. Our analysis documents the value of what was destroyed, the weak resistance mounted by the Australian economics profession during this period, and the role played by many Australian economists as apologists for Australia's most catastrophic peacetime economic policy failure. We close with ideas for working towards a better future.
Keywords: I31; I38; A11; 330; COVID-19; economics profession; WELLBY; welfare; health policy; Australia